The study of religion and theology at the University of Pretoria – A century of endeavour in conditionalistic perspective - Krüger, J. S. (HTS teologiese studies, 2016)
This article suggests a theoretical and methodological perspective primarily hinging on the categories of Horizon, Totality and conditionalism, with an outspoken mystical orientation, radically relativising yet simultaneously treasuring diverse religious expression. This model was developed with a view to interpreting the history of religions, in this case applied to the history of the Faculty of Theology at the University of Pretoria from 1917 to 2017.Utilising this perspective, the history of the faculty is analysed in terms of three qualitatively distinct yet continuous epochs, overlapping with the three epochs of South African history during the twentieth century: 1902–1948, 1948–1994 and 1994 to present. In particular the article focuses on two dimensions of theological existence at the University of Pretoria: firstly, its interaction with the state over this century, that is, its political existence during the decades prefiguring apartheid, during apartheid and during the aftermath of apartheid; secondly, its relationship with the wider world of religious pluralism over the past century, implying its notion of religious truth. Differences of emphasis and conflicts during the century, involving both sets of problems, are explained and understood conditionalistically and with reference to Totality and Horizon. Racial exclusion and religious exclusion are understood as mutually determining and are both informed by and dependent on a certain view of religious truth.In the context of its own ambit this article has a reconciliatory intention, not evaluating the mistakes of the past in terms of the categories of sin and guilt, but rather in terms of tragic misjudgements of situations: shortcomings in historical hindsight, sufficiently wide peripheral vision, realistic foresight and sufficient insight into the epochal conditions of the times and the essence of religion. Greed and hatred, seemingly ingrained in human nature, are taken to feed on such lack of insight.